2016
DOI: 10.1002/cne.24143
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular organization of UBE3A in neurons

Abstract: Ubiquitination regulates a broad array of cellular processes, and defective ubiquitination is implicated in several neurological disorders. Loss of the E3 ubiquitin-protein ligase UBE3A causes Angelman syndrome. Despite its clinical importance, the normal role of UBE3A in neurons is still unclear. As a step toward deciphering its possible functions, we performed high-resolution light and electron microscopic immunocytochemistry. We report a broad distribution of UBE3A in neurons, highlighted by concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 53 publications
2
11
0
Order By: Relevance
“…1J). We therefore concluded that a large portion of UBE3A molecules was localized in the nucleus of neurons, which is consistent with the results of a recent study (35).…”
Section: Ube3a Is Localized To the Nucleus Of Neuronssupporting
confidence: 93%
“…1J). We therefore concluded that a large portion of UBE3A molecules was localized in the nucleus of neurons, which is consistent with the results of a recent study (35).…”
Section: Ube3a Is Localized To the Nucleus Of Neuronssupporting
confidence: 93%
“…Additionally, reduced function of complex III in patients with the 15q11-q13 duplication syndrome has been documented [154]. The role of mitochondria has been studied mainly in AS mouse models, like the heterozygous mice Ube3a m-\p+ [155], in which Ube3a was found in close proximity to the outer mitochondrial membrane [156]. Mitochondrial morphological changes in the CA1 hippocampal region were found, like smaller mitochondria and disturbances in mitochondrial cristae compared to WT littermates [157].…”
Section: Syndromic Asd Caused By 15q11-q13 Deletions Microdeletionsmentioning
confidence: 99%
“…Mice express two protein isoforms, isoforms 2 and 3, which are highly homologous to the human isoforms 3 and 1, respectively (Avagliano Trezza et al, 2019; Greer et al, 2010). In human and mouse neurons UBE3A is mainly localized to the nucleus with smaller amounts present in axons and dendrites (Avagliano Trezza et al, 2019; Burette et al, 2016, 2018; Dindot, Antalffy, Bhattacharjee, & Beaudet, 2008). Recent work in mice has revealed how this subcellular distribution of UBE3A is achieved: the short isoform (mUBE3A Iso3), which constitutes ~80% of total UBE3A, is mainly nuclear while the, less abundant, long isoform (mUBE3AIso2) is predominantly present in the cytosol (Avagliano Trezza et al, 2019; Miao et al, 2013).…”
Section: Introductionmentioning
confidence: 99%